2017
DOI: 10.1177/1098612x17700808
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of external ear disorders in Belgian stray cats

Abstract: Objectives Feline otitis externa is a multifactorial dermatological disorder about which very little is known. The objective of this study was to map the prevalence of external ear canal disorders and the pathogens causing otitis externa in stray cats roaming around the region of Ghent, Belgium. Methods One hundred and thirty stray cats were randomly selected during a local trap-neuter-return programme. All cats were European Shorthairs. This study included clinical, otoscopic and cytological evaluation of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 22 publications
4
18
2
Order By: Relevance
“…5,6,12 This study found that the prevalence of O cynotis was low, recorded as 0.9%. This result is in agreement with a Belgian study (2%), 10 an Australian study (<0.1%) 13 and a Portuguese study (2.2%). 19 Far higher numbers were reported in a Greek study (25.5%), 20 an Italian study (29.4%) 11 and in a study from the USA (37%).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…5,6,12 This study found that the prevalence of O cynotis was low, recorded as 0.9%. This result is in agreement with a Belgian study (2%), 10 an Australian study (<0.1%) 13 and a Portuguese study (2.2%). 19 Far higher numbers were reported in a Greek study (25.5%), 20 an Italian study (29.4%) 11 and in a study from the USA (37%).…”
Section: Discussionsupporting
confidence: 93%
“…Only low numbers of saprophytes were found compared with a previous study, 10 most likely because most of the rescue cats were mainly housed indoors at time of sampling. The cats in this study were sampled throughout the spring and summer.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…[1][2][3][4] It is a common ailment in small animals, occurring in 13-16% of the canine case population; 1 however, few data concerning the prevalence and incidence of feline otitis externa have been published. 2 The primary causes of this ailment are those that induce otitis externa directly; for example, foreign bodies or ectoparasites are the most common causes of feline external otitis. 3,4 Although some allergic cats will have concurrent otitis, the incidence is far lower than in dogs.…”
Section: Introductionmentioning
confidence: 99%